A Review of Near-Memory Computing Architectures: Opportunities and Challenges - Singh, Gagandeep; Chelini, Lorenzo; Corda, Stefano; Javed Awan, Ahsan; Stuijk, Sander; Jordans, Roel; Corporaal, Henk; Boonstra, Albert-Jan (2018 21st Euromicro Conference on Digital System Design (DSD), 2018)
The conventional approach of moving stored data to the CPU for computation has become a major performance bottleneck for emerging scale-out data-intensive applications due to their limited data reuse. At the same time, the advancement in integration technologies have made the decade-old concept of coupling compute units close to the memory (called Near-Memory Computing) more viable. Processing right at the "home" of data can completely diminish the data movement problem of data-intensive applications. This paper focuses on analyzing and organizing the extensive body of literature on near-memory computing across various dimensions: starting from the memory level where this paradigm is applied, to the granularity of the application that could be executed on the near-memory units. We highlight the challenges as well as the critical need of evaluation methodologies that can be employed in designing these special architectures. Using a case study, we present our methodology and also identify topics for future research to unlock the full potential of near-memory computing.